Hemoglobin Nanocrystals for Drugs Free, Synergistic Theranostics of Colon Tumor (Small 8/2023). Issue 8 (22nd February 2023) - Zhou, Renbin; Xu, Hao; Qu, Junle; Ohulchanskyy, Tymish Y.
Abstract : Drug Free Tumor Theranostics In article number 2205165, Tymish Y. Ohulchanskyy and co‐authors introduce hemoglobin nanocrystals for drug free, synergistic and selective theranostics of colon cancer. After intravenous (i.v.) injection, these nanocrystals target colon tumor and react with tumor‐specific H2 S and H2 O to enable magnetic resonance imaging guided photothermal therapy and produce OH for chemodynamic therapy.